Od geniuszu do wielkoduszności. Rola kultury w wychowaniu do patriotyzmu - Chłodna-Błach, Imelda (Fides, Ratio et Patria. Studia Toruńskie, 2018)
In this text, we have attempted to answer the question: what characterizes the Great Poles? In what culture did they grow? They were Poles not only because of their origin or nationality, but also because of the culture in which they were brought up, which shaped their ethos. In their formation a significant role was played by a thorough education – on this way they developed their talent, sometimes a genius. The second important thing was the upbringing of character. Education is the basis of culture, because culture is conveyed through education. Both of these elements – education and training are of great importance in shaping a high culture in a person. And this culture is national culture. It is an elitist culture - in the sense that it requires getting the right level of education – and in many different areas – so that you can live it. We acquire it by reading appropriate literature, growing in the right environment. The message of national culture is based on tradition, which is first conveyed by the house, then the school, then the state and the church. Aristotle noticed that the virtue that most characterizes a man representing high culture is the virtue of magnanimity. The purpose of magnanimity is the spiritual greatness of man, and therefore his high culture. A generous man considers himself worthy of great things and deserves it indeed. Magnanimity (generosity) is one of the keystones of our moral life.